1998
DOI: 10.1016/s0014-5793(98)00323-8
|View full text |Cite
|
Sign up to set email alerts
|

A transcription frame‐based analysis of the genomic DNA sequence of a hyper‐thermophilic archaeon for the identification of genes, pseudo‐genes and operon structures

Abstract: An algorithm for identifying transcription units, independently regulated genes and operons, and pseudo-genes that are not expected to be expressed, has been developed by combining a system for predicting transcription and translation signals, and a system for scoring the triplet periodicity in ORF candidates. By using the algorithm, the 1.09 Mb sequence that covers approximately 60% of the genome of Pyrococcus sp. OT3 has been analyzed. The identified ORFs show the expected biological and physical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…For initiation of transcription, TATA-binding protein and transcription factor B are required. The transcription signals identified upstream of putative genes in Pyrococcus OT3 (OGT of 98°C) were closer to AAAATTTATAAA (16), whereas those identified in T. volcanium in this study were closer to AAAATTTATATA. The consensus sequence of Pyrococcus OT3 has a higher equilibrium binding constant to TATA-binding protein, as the consensus sequence of T. volcanium has a higher Each column is composed of 750 lines from top to bottom, and each line is an assembly of 105 microsquares from left to right.…”
Section: Methodscontrasting
confidence: 41%
See 1 more Smart Citation
“…For initiation of transcription, TATA-binding protein and transcription factor B are required. The transcription signals identified upstream of putative genes in Pyrococcus OT3 (OGT of 98°C) were closer to AAAATTTATAAA (16), whereas those identified in T. volcanium in this study were closer to AAAATTTATATA. The consensus sequence of Pyrococcus OT3 has a higher equilibrium binding constant to TATA-binding protein, as the consensus sequence of T. volcanium has a higher Each column is composed of 750 lines from top to bottom, and each line is an assembly of 105 microsquares from left to right.…”
Section: Methodscontrasting
confidence: 41%
“…1 A and C, gene-coding regions can be visualized as stripes in red and black, where regions are coding for genes along the strand of the sequence shown, or stripes in yellow and white, where regions are coding for genes along the complementary strand. These stripes are created because in gene-coding regions purines are more frequent than pyrimidines as a consequence of the triplet periodic combination (16,29). The average number of bases in genes is approximately 1,000; thus, in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary work shows that alignment of multiple codons within one gene also shows periodicity. This agrees with work done for some genes in Pyrococcus [13]. There has been some suggestion that examination of periodicity within ORFs could assist in gene identification [14].…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, it is well known that there are many pseudogenes in intergenic regions of prokaryotic and eukaryotic DNA sequences. [27][28][29] Harrison et al 28 have analyzed pseudogenes in the worm and found that there is about one pseudogene for every eight genes. Pseudogenes also exist in each human chromosome.…”
Section: Frame Independence Of the Algorithmmentioning
confidence: 99%